Utilization of Microsoft Power Point Media in Mahārah Istimā’ (Arabic Learning Skill) Learning in the Digital Age/ Pemanfaatan Media Microsoft Power Point dalam Pembelajaran Mahārah Istimā’ (Kemahiran Mendengar) di Era Digital - Wahyu Rahmadsyah Berutu; Muhammad Jafar Shodiq; Yuniar (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
In the current digital era, an educator is required to be able to utilize various technological media as an alternative to support learning activities. The purpose of this article is to provide an overview and insight regarding the use of Microsoft PowerPoint in mahārah istimā' learning, both online and offline. This study used descriptive qualitative methods, while data collection utilized observation, documentation, and questionnaires. The data analysis stage in this study used the model of Miles and Huberman which consists of three paths, namely data reduction, data presentation, and drawing or conclusions. Based on the results, PowerPoint is able to help educators create and deliver mahārah istimā' learning, and can facilitate students acquisition and understand the lecture. Specifically, the advantages of learning mahārah istimā' using the PowerPoint are being able to combine images and audio, using the learner’s own voice, using Arabic audio such as al-Arabiyah Bayna Yadaik MP3, or using a native speaker’s illustrations with writing through the narakeet.com website, which is applied in this research. Materials that have been uploaded into the PowerPoint can be saved in PDF and MPEG-4 video formats so that students can study them independently. The contents of the learning materials, both images, and audio can also be changed as needed. Abstrak Di era digital saat ini seorang pendidik dituntut untuk mampu memanfaatkan berbagai media teknologi sebagai alternatif untuk mendukung aktivitas pembelajaran. Tujuan dari artikel ini adalah untuk memberikan gambaran dan wawasan terkait pemanfaatan Microsoft Power Point dalam pembelajaran mahārah istimā’, baik secara daring maupun luring. Metode dalam penelitian ini menggunakan metode kualitatif deskriptif, sedangkan pengumpulan data menggunakan metode observasi, dokumentasi, dan kuisioner. Analisis data penelitian ini menggunakan model Miles dan Huberman yang terdiri dari tiga alur yaitu reduksi data, penyajian data, dan penarikan atau kesimpulan. Berdasarkan hasil penelitian, Media Power Point dapat membantu pendidik dalam membuat dan menyampaikan pembelajaran mahārah istimā’, serta memfasilitasi peserta didik menerima dan mengerti materi pembelajaran. Secara spesifik kelebihan pembelajaran mahārah istimā’ menggunakan Power Point adalah bisa memadukan antara gambar dan audio, baik menggunakan suara sendiri, audio bahasa Arab seperti al-Arabiyah Bayna Yadaik MP3, atau audio bahasa Arab dengan tulisan melalui website narakeet.com. Materi yang telah diuppload ke dalam Power Point bisa disimpan dalam format PDF dan video MPEG-4, sehingga peserta didik bisa mempelajarinya secara mandiri. Konten materi pembelajaran baik gambar maupun audio juga bisa diubah sesuai dengan kebutuhan.